Prevalensi fraktur terbuka ekstremitas bawah grade III di RSUP Sanglah Denpasar periode bulan Januari - Juli tahun 2014 - Gusti Made Laksmana Aris Saputra; I Gede Eka Wiratnaya (Universitas Udayana, 2018)
The open fractures are fractures which the bone throughout the skin, it can be infected by the outside effect of the body. The complication fracture is it come of complications such as malunion, delayed union, nounion and bone infections. The age group most susceptible to get this facture is the age group of adolescents and adults. The open Ekretremitas fractures of Type III, in the adult group have a significant impact. The diagnosis of open extremity fractures grade III will be able to directly diagnosed by physical examinationThis research is a descriptive research used by retrospective descriptive study draft of the patients with lower limb open fracture grade III in General Hospital Sanglah period from January to July 2014. The subjects were patients with open fractures of the lower limb of grade III are treated in the Central Public Hospital of Sanglah the subject selection used by total sampling method.The results have to be found of lower limb open fracture grade III in the children group , patients suffering from lower extremity open fracture type III, there is no data in male and there is 1 sample in female (100%). In the adolescent age group, patients suffering from lower extremity open frakur type III there are 7 samples in male (63.6%), and 4 samples in female (36.4%). In the group of early adulthood, patients suffering from lower extremity open frakur type III, there are 4 samples in male (80%), and 1 sample in female (80%). In the age group of middle adulthood, patients suffering from lower extremity open frakur grade III there are 4 samples in male (66.7%), and 2 samples in female (33.3%). In the age group of elderly patients suffering from lower extremity open frakur grade III- there is no data in male and 1 sample in female (100%). All lower limb open fracture grade III in General Hospital Sanglah caused by traffic accidents (traffic accident). Keywords: lower limb open fracture grade III, kids, teens, early adulthood, middle age, elderly